Farmers Attitude Towards Using Agro-Chemicals in Rice Production: A Case in Laxmipur District of Bangladesh (The Agriculturists, 2016)
The study was conducted to determine the farmers attitude towards using agro-chemicals in rice field in Laxmipur district of Bangladesh. Data were collected from seventy farmers following simple random sampling technique, complied and interpreted as per objectives of the study. Most of the farmers were middle aged, had primary level of education with small farm size, medium extension media contact with an average family annual income of about 1350 USD. About 87% of the farmers had low to medium knowledge on use of agro-chemicals in rice cultivation. About 74% of the farmers had moderately favorable attitude towards using agro-chemicals. Family annual income, extension media contact and knowledge on agro-chemical were the most important factors that affect the attitude of the farmers towards using agro-chemicals in crop production. Therefore it is recommended that arrangement of need based training with more extension contact for the farmers will be helpful to improve the behavior of using agro-chemicals.The Agriculturists 2015; 13(2) 105-112